‘The shock of diagnosis’: Qualitative accounts from people with Motor Neurone Disease reflecting the need for more person-centred care - Aoun, Samar; O'Brien, M.; Breen, Lauren; O'Connor, M. (Elsevier, 2018)
The diagnosis of Motor Neurone Disease (MND) is devastating for people with MND (PwMND) and their families. The objective of this study is to describe the experiences of PwMND in receiving the diagnosis in order to inform a more person-centred approach to communicating such bad news. The design was an anonymous postal survey facilitated by all MND associations across Australia (2014–15). Survey questions centred on the SPIKES protocol for communicating bad news; each question contained an area for written responses, which were thematically analysed for content. Two hundred and forty-eight responses were received from people with MND (29% response rate). Four themes emerged: challenges in being diagnosed with MND; the emotions experienced; the good and the bad; and links to further information and support. Receiving such a diagnosis requires preparation, forethought, sensitive and individualised care on the part of the neurologist, including where and how the diagnosis is given; the supports required; and timing, amounts and sources of giving information. The emotional reactions of the neurologist also caused a lasting impression on those receiving the diagnosis. This study could form the basis for best practice programs implementing a more person-centred approach to caring for PwMND right from the diagnosis stage. The focus needs to shift on the person's values, preferences, psychosocial and existential concerns in the context of the underlying disease experience and the manner clinical practice is delivered.